1997
DOI: 10.1103/physrevb.55.5006
|View full text |Cite
|
Sign up to set email alerts
|

Core effects in lithium hydride

Abstract: Calculations of the directional Compton profiles and of the anisotropies of Compton scattering are reported, based on density-functional theory within the local-density approximation, performed using a plane-wave basis, and using ͑i͒ pseudopotentials and ͑ii͒ full, unscreened Coulomb potentials for both Li and H atoms. The pseudopotential calculations yield Compton profiles with unsatisfactory agreement with experiment. The reason of this failure is discussed. It is then shown that, with the total Coulomb pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Bellaiche and Kunc [28] obtained convergence in the structural properties of solid LiH with a plane-wave cutoff of the order of 200 Ry and the valence Compton profiles were in good agreement with the ones reconstructed by simply orthogonalizing the valence wave functions to a core atomic orbital. Similarly, we find that the valence orbitals of lithium are well converged at about 300 Ry and increasing the plane-wave cutoff to 400 Ry has a negligible effect on the valence Compton profiles.…”
Section: Appendix B: Full-core Plane-wave Lda Calculationsmentioning
confidence: 63%
See 1 more Smart Citation
“…Bellaiche and Kunc [28] obtained convergence in the structural properties of solid LiH with a plane-wave cutoff of the order of 200 Ry and the valence Compton profiles were in good agreement with the ones reconstructed by simply orthogonalizing the valence wave functions to a core atomic orbital. Similarly, we find that the valence orbitals of lithium are well converged at about 300 Ry and increasing the plane-wave cutoff to 400 Ry has a negligible effect on the valence Compton profiles.…”
Section: Appendix B: Full-core Plane-wave Lda Calculationsmentioning
confidence: 63%
“…To account for the correct oscillatory behavior of the valence wave functions, the valence orbitals are usually computed within traditional all-electron schemes (LAPW or LMTO) or, alternatively, the true valence wave functions are reconstructed from the pseudized orbitals [26,27]. On the other hand, several calculations in the literature have shown the feasibility of plane-wave calculations using the unscreened Coulomb potential for first-row elements [19,28,29]. We therefore decided to follow this more straightforward route and adopt a plane-wave basis also with the −3/r potential of lithium.…”
Section: Appendix B: Full-core Plane-wave Lda Calculationsmentioning
confidence: 99%
“…Further, it also shows the different possible c/a/c/a domain types, with the boxed inset in Figure 1e magnified to render a clearer image of the varying ferroelastic domain arrangements with different angles of orientations (denoted by arrows). To probe if the changes in the domain patterns are due to an electric-field-induced phase transition (as postulated by Fu et al [29] and Bellaiche et al [30] ), we have studied the effect of electric field on the X-ray-diffraction (XRD) pattern of the film using a lab diffractometer (Bruker D8). The smallest possible spot size for the X-ray beam was %3 mm 2 , and this meant that an array of capacitors had to be tested (see Experimental section for details).…”
mentioning
confidence: 99%
“…A few theoretical works which proceed along similar lines as our present work deserve to be mentioned: the pseudopotential calculations of w x Com pton profiles in beryllium 4 , the w x Hartree᎐Fock calculations on LiH and BN 5 , the works on graphite and intercalation compounds w x 6᎐8 , still another pseudopotential calculation on w x BN 9 , and, finally, our previous work in LiH within the Hartree᎐Fock theory and in the basis of w x Wannier-type functions 10 . A more exhaustive w x review can be found, e.g., in 3 .…”
Section: Introduction Lthough the Compton Effect Has Been Knownmentioning
confidence: 64%